Bilateral mucoid degeneration of the posterior cruciate ligaments - AP Parkar; FM Vanhoenacker; ME Adriaensen (Journal of the Belgian Society of Radiology, 2013)
Mucoid (myxoid) degeneration of the anterior cruciate ligament (ACL) is well documented and well known. Mucoid degeneration of the posterior cruciate ligament (PCL) has been reported, but is rare in comparison. The changes may be subtle and may be missed if one is not aware of the diagnosis. As in the ACL, degeneration may cause pain and discomfort. Recognition of the pathology and correct diagnosis is important for the patient and referring physician, as this may have an impact on the therapeutic strategy. We present a case of mucoid degeneration of both PCLs, which to the best of our knowledge has not been published before in the medical literature, as a probable cause of knee pain due to habitual kneeling.